Comprehensive analysis of polymorphisms in the HLA‐G 5′ upstream regulatory and 3′ untranslated regions in Brazilian patients with systemic lupus erythematosus. Issue 6 (11th March 2015) - Catamo, E.; Addobbati, C.; Segat, L.; Sotero Fragoso, T.; Tavares Dantas, A.; de Ataide Mariz, H.; Ferreira da Rocha Junior, L.; Branco PintoDuarte, A. L.; Coelho, A. V. C.; de Moura, R. R.; Polesello, V.; Crovella, S.; et al.
Abstract This study aims to comprehensively analyze human leucocyte antigen (HLA)‐G polymorphisms association with susceptibility to systemic lupus erythematosus (SLE) development and clinical manifestations. The HLA‐G 5′ upstream regulatory region (URR), 3′ untranslated region (UTR) and a cytosine deletion at exon 3 (ΔC, HLA‐G*0105N allele) were analyzed in 114 SLE patients and 128 healthy controls from North East Brazil. The +3003T>C (rs1707) C allele and the HG010101c extended HLA‐G allele were significantly more frequent in SLE patients than healthy controls (+3003C allele frequency: 12% in SLE patients vs 6% in controls; odds ratio (OR), 2.10, 95% confidence interval (CI), 1.06–4.28, P = 0.026; HG010101c frequency: 11.8% in SLE patients and 6.3% in controls; OR, 2.14, 95% CI, 1.01–4.51, P = 0.046) and were associated with susceptibility for disease development. Other polymorphisms were associated with different clinical manifestations. Although HLA‐G role in SLE disease is far from being elucidated yet, our association study results along with a systematic review and meta‐analysis suggest that HLA‐G might be able to slightly modulate the complex SLE phenotype (pooled OR, 1.14, 95% CI, 1.02–1.27, P = 0.021).